PENGARUH DIKLAT, DISIPLIN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT. MEDCO E & P INDONESIA SOUTH SUMATERA BLOCK - Baidowi Abdhie; Sahyuni . (JURNAL KOMPETITIF, 2018)
The Influence analysis of Training and education, Discipline and Motivation toward Employee at PT. Medco  Sumatera BlockE & P Indonesia South Sumatera Block.This research studies the influence of Training and education, Discipline and Motivation toward Employee at PT. Medco  Sumatera BlockE & P Indonesia South Sumatera Block. The research of this case study aims to know the influence of Training and education, Discipline and Motivation toward Employee at PT. Medco  Sumatera BlockE & P Indonesia South Sumatera Block either through parsial and also together. The population In this research are the Officer at PT. Medco  Sumatera BlockE & P Indonesia South Sumatera Block, totally 120 people and sampling 119 people.From data-processing result known that regression coefficient for variable of Training and education (X1) equal to 0,416 with significant level equal to 5%, Discipline     ( X2) equal to 0,574 with significant level equal to 5%, regression coefficient for variable of Motivation ( X3) equal to 0,180 with significant level equal to 5%, while value of constant inset equal to 10,636, so that doubled regression equation of this research is : Ý = 10,636 + 0,416X1 + 0,574X2 + 0,180X3  Keyword : Training and education, Discipline, Motivation and Employee